Further evaluation of observational and mechanical measures of physical activity. (1st February 2018) - Van Camp, Carole M.; Berth, Diane
Abstract : Recent behavioral research has used a variety of methods to quantify physical activity, including direct observation using the Observational System for Recording Physical Activity (OSRAC), and automated devices such as heart rate (HR) monitors, pedometers, and Fitbit Accelerometers. The current study evaluated the concurrent validity of these measures, as well as the reliability of the pedometers and Fitbits. Four children engaged in 15 activities listed in the OSRAC coding system while their HRs and steps taken were measured. The results indicated that for most activities, HR covaried with the OSRAC activity levels, although some exceptions were noted. Steps per minute as measured by the Fitbit also covaried with the OSRAC activity levels and Fitbit data were reliable when activities did not involve subjects losing contact with the ground. Pedometers produced similar but less reliable steps per minute data.